EVALUATION OF THE IMPLEMENTATION OF THE INDEPENDENT ACADEMIC INFORMATION SYSTEM (SIAMIR) AT STIKOM UYELINDO USING THE DELONE AND MCLEAN MODEL - Bulan, Semlinda Juszandri (Universitas Nusa Cendana, 2025)
Academic information systems are a crucial element in supporting the effectiveness and efficiency of academic management at universities. STIKOM Uyelindo uses an academic information system called SiAmir to serve the academic administration needs of students, lecturers, and staff. However, the success of this system's implementation needs to be systematically evaluated to ensure its continued improvement. This study aims to evaluate the implementation of SiAmir using the DeLone and McLean model, which consists of six variables: system quality, information quality, service quality, system usage, user satisfaction, and net benefits. Respondents in this study were 165 students and lecturers at STIKOM Uyelindo. The data analysis method used was Partial Least Squares (PLS) and was run using SmartPLS version 3.0 software. The results showed that six hypotheses were accepted and three were rejected. Information Quality and Service Quality significantly influenced User Usage and Satisfaction, while System Quality had no significant effect. User Satisfaction proved to be a key mediator with the strongest influence on Net Benefits, while Usage had no direct effect. The findings confirm that information system success is determined more by the quality of content and services than by technical aspects, with user satisfaction being the primary mediating factor. Practical implications suggest that organizations need to prioritize investments in information and service quality to maximize the benefits of information systems.